ANGLICISMS IN YOUTH SLANG - Kamalatdinova, Dinara Maratovna; Kabulova , Lola Tolibayevna (Educational Research in Universal Sciences, 2023)
This study is devoted to identifying English borrowings in youth slang inherent in the generation of "millennials" - young people from 14 to 35 years old, born in the period close to the turn of the millennium. A lot of scientific works are devoted to the phenomenon of youth slang, the definition of its boundaries, functions and description criteria. The most relevant of them focus on the youth slang of the 2010s. There are studies of the problem of English borrowings and English influence in modern Russian language. However, the influence of the English language on the slang of modern youth has been little studied. We believe that the rapid growth in the number of borrowings in this area requires close attention and scientific analysis. The slang of "millennials" is presented in numerous humorous Internet publications, but unlike the slang of the previous generation, it is not described from a scientific point of view. The purpose of our work was to identify new English borrowings, highlight their lexical and grammatical features in comparison with borrowings from previous years. The relevance of this work is due to the attention to the slang of today’s youth in the aspect of globalization processes. In the study the methods of studying the works of linguists, the analysis of Internet publications and dictionary data, a survey of informants, and diachronic comparison were used. As a result of the analysis of the collected material, an increase in the number of anglicisms was noted compared to the 2010s, revealed some features of the formation of lexical meanings and grammaticalization of new ones lexical units. Youth slang is a reflection of modern social phenomena, and its study is of interest not only to linguists, but also to culturologists, sociologists, and psychologists.